The myth of the universal adult educator: A literature review. - Angela Humphrey Brown (Adult Education Research Conference, 1997)
This paper critically evaluates the adult education literature with respect to how it deals with the race and the gender of the teachers as a factor in the teaching-learning environment. The mainstream literature perpetuates the myth of the universal teacher while the narratives of African American women transcend the myth.